Genetic differentiation of Turkish Althaea L. and Alcea L. species - Öztürk, Fatma; Babaoğlu, Selcen; Uzunhisarcıklı, M. Erkan; Açık, Leyla; Vural, Mecit; Gürcan, I. Sefa (İstanbul Kültür Üniversitesi, 2009)
Random amplified polymorphic DNA (RAPD) analysis and SDS-PAGE analysis of total seed proteins were used to estimate genetic differences between/within four Althaea (Malvaceae) and eighteen Alcea species. The 4 Althaea and 18 Alcea species were found to have species-specific protein profiles. The total of 223 different RAPD bands for Althaea species were generated by the 11 primers and total of 116 different RAPD bands by the 8 random primers for Alcea species. The results of the POPGENE cluster analysis were in broad agreement with previous morphological classifications of these four species. Statistical significance within Alcea and Althaea population was tested using of molecular variance (AMOVA) approach used in Arlequin. According to the results, there is a large genetic differentiation between species A. hirsuta with A. armeniaca, A. officinalis with A. hirsuta, FST 0.24 and FST 0.21, respectively. There is also wide differentiation between Alcea species. FST statistics range from 0,126 (A. guestii between A. striata ssp. striata) to 0,685 (A. biennis between A. acaulis). The results suggest that RAPD and SDS-PAGE markers can be used to reveal genetic differentiation between species and genus.
Keywords: Althaea, Alcea; RAPD-PCR; SDS-PAGE